Does foreign direct investment reduce poverty? Empirical evidence from Tanzania - M. T. Magombeyi; N. M. Odhiambo (SPOUDAI - Journal of Economics and Business, 2017)
This paper investigates the direct impact of foreign direct investment (FDI) inflows on poverty reduction in Tanzania between 1980 and 2014. The paper attempts to answer one critical question: Does FDI reduce poverty in Tanzania? The study employs three poverty reduction proxies, namely, household consumption expenditure (Pov1), infant mortality rate (Pov2), and life expectancy (Pov3). The three poverty reduction proxies have been selected based on the need to capture poverty in its multidimensional nature. Using the autoregressive distributed lag (ARDL) bounds testing approach, the study finds that FDI has a short-run positive impact on poverty reduction when infant mortality rate is used as a proxy for poverty reduction. However, when infant mortality rate and life expectancy care used as poverty reduction proxies, FDI has no impact on poverty reduction. This applies irrespective of whether the analysis is conducted in the short run or in the long run. The study, therefore, concludes that the impact of FDI on poverty reduction is sensitive to the proxy used to measure the level of poverty reduction, and varies over time.
Keywords: F21; I32; 330; Tanzania; Poverty Reduction; Foreign Direct Investment; Household Consumption Expenditure; Infant Mortality Rate; Life Expectancy